2009
DOI: 10.1111/j.1467-9396.2009.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Output Volatility: A Theoretical Approach*

Abstract: This paper makes an attempt to determine the factors influencing exchange rate and exchange rate uncertainty, as well as output and output variability. In the context of a small open economy under flexible exchange rates regime it is found that the level both of exchange rate and output is affected by monetary and inflationary shocks, as well as shocks in government spending, output, and trade balance. Further, the uncertainty of exchange rate and output is associated positively with the uncertainty of all sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It has positive and insignificant effect on volatility in PKR-JPY exchange rates. The insignificance of real output volatility is in line with Morana (2009) and Grydaki and Fountas (2009) and positive effect is in line with Friedman (1953) where output volatility amplifies exchange rate volatility. The foreign reserves volatility has negative and significant effect on volatility in PKR-USD and PKR-GBP exchange rates.…”
Section: Empirical Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…It has positive and insignificant effect on volatility in PKR-JPY exchange rates. The insignificance of real output volatility is in line with Morana (2009) and Grydaki and Fountas (2009) and positive effect is in line with Friedman (1953) where output volatility amplifies exchange rate volatility. The foreign reserves volatility has negative and significant effect on volatility in PKR-USD and PKR-GBP exchange rates.…”
Section: Empirical Analysissupporting
confidence: 79%
“…Hviding et al (2004) has found higher international reserves reduce exchange rate volatility. Grydaki and Fountas (2009) have found that variability in the money supply, inflation and output explains variability in exchange rates. Morana (2009) have found that that exchange rate volatility is affected by the monetary shocks particularly output and inflation volatility.…”
Section: A Review Of Empirical Studies On Exchange Rate Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The seemingly mixed results from empirical studies, while suggesting that the effect of exchange rate volatility on trade might be an empirical issue, may also reflect the emptiness of theoretical results in the general equilibrium models; they allude t o the fact that inconsistency in exchange rates is contingent on the volatility of underlying shocks to policies, preferences, and technology, to the overall policy regime (Clark et al, 2004). Meaning, exchange rate swings may be as a result of simply the changes in the volatility of rudimentary shocks propagated by the Driskill-McCafferty model (Grydaki and Fountas, 2009).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Even though the switch to floating exchange rate gives autonomy to the monetary authorities in the management of monetary policy thereby allowing changes in the exchange rate to be dictated by fluctuating market conditions, the situation still generates instability in the exchange rate capable of inflicting significant costs on the economy compared to the expected gains (Grydaki & Fountas, 2009;McKenzie, 1998). On the other hand, under the regime of the fixed exchange rate, exchange rates that are misaligned inflicted costs on the economy.…”
Section: Introductionmentioning
confidence: 99%